2020
DOI: 10.1051/e3sconf/202020004005
|View full text |Cite
|
Sign up to set email alerts
|

Population characteristics and distribution patterns of slum areas in Palembang City: Getis ord gi* analysis

Abstract: The paper aims to describe the population characteristics and the distribution patterns of slums in Palembang City. The research employs a quantitative method with 382 respondents. The data are analyzed using cross-tabulation of IBM SPSS 23 to know the population characteristics. Meanwhile, the distribution patterns of slums are analyzed by observing the sample distribution through the proportional random sampling technique. It is carried out by calculating the number of buildings of each area and noting the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The average value is filled, and the true meaning of each cube bin (as shown in Figure 2b) is the average deformationin (Prasannakumar et al, 2011) The spatio-temporal hotspot analysis algorithm is shown in Figure 2c. Firstly, the spatio-temporal Getis-Ord Gi * statistics (Sukmaniar et al, 2020) (as Equations 1) are performed on each bin to obtain the z-score value of each bin, that is, the continuous deformation value in the cumulative deformation period is obtained. Then, based on this value, the K nearest neighbor clustering algorithm is used in the space-time domain to obtain the deformation hot and cold spots in the demonstration area.…”
Section: Emerging Spatial and Temporal Hotspot Analysis Methodologymentioning
confidence: 99%
“…The average value is filled, and the true meaning of each cube bin (as shown in Figure 2b) is the average deformationin (Prasannakumar et al, 2011) The spatio-temporal hotspot analysis algorithm is shown in Figure 2c. Firstly, the spatio-temporal Getis-Ord Gi * statistics (Sukmaniar et al, 2020) (as Equations 1) are performed on each bin to obtain the z-score value of each bin, that is, the continuous deformation value in the cumulative deformation period is obtained. Then, based on this value, the K nearest neighbor clustering algorithm is used in the space-time domain to obtain the deformation hot and cold spots in the demonstration area.…”
Section: Emerging Spatial and Temporal Hotspot Analysis Methodologymentioning
confidence: 99%
“…The effect on population density brings the investors to develop petrol stations. The analysis using Getis Ord Gi* reveals that the slum areas in the city centre and the dense population is a cold spot (low cluster), while those that are far from the city centre are hot spots as high cluster (Sukmaniar et al, 2020) . The result obtained from the spatial analysis will determine and identify the strategic location for future planning.…”
Section: Materials and Techniquementioning
confidence: 99%
“…The riverbanks provide an alternative housing option for residents seeking low rental costs. Like other urban areas, this city always experiences an increase in population yearly (Sukmaniar, Pitoyo et al, 2020). This phenomenon stems from the bustling economic activities in Palembang City service and trade sectors.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, establishing strong collaboration becomes essential to maintain orderliness in infrastructural development. Urbanization continues due to the high migration of people to urban areas with increased economic activity (Sukmaniar, Kurniawan et al, 2020). This phenomenon is a result of the strong attraction that urban areas hold for migrants who aspire to enhance their social and economic conditions.…”
Section: Introductionmentioning
confidence: 99%